2012
DOI: 10.1111/j.1442-2018.2011.00672.x
|View full text |Cite
|
Sign up to set email alerts
|

Health according to the experiences of Iranian women with diabetes: A phenomenological study

Abstract: This study explores the meaning of health among Iranian women with diabetes using hermeneutic phenomenology based on Van Manen's approach. A total of 19 women with diabetes who were referred to the Diabetes Center of Imam Khomeini hospital in Ardabil, Iran were recruited using a purposive sampling method. Data were gathered through semi-structured interviews. Each interview was transcribed verbatim and analyzed simultaneously. Data analysis led to the emergence of five main themes: a God-centered life, health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…Nearly half (45.6 %) prayed privately at least once a day. Aghamohammadi-Kalkhoran et al (2012) reported that most diabetic patients have a close relationship with God and regularly perform private religious practices such as praying, reciting the Quran, Do'a, and Dhikr. Similarly, Arcury et al (2007) found that 83.0 % of the diabetic patients prayed privately at least once a day.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nearly half (45.6 %) prayed privately at least once a day. Aghamohammadi-Kalkhoran et al (2012) reported that most diabetic patients have a close relationship with God and regularly perform private religious practices such as praying, reciting the Quran, Do'a, and Dhikr. Similarly, Arcury et al (2007) found that 83.0 % of the diabetic patients prayed privately at least once a day.…”
Section: Discussionmentioning
confidence: 98%
“…Gutierrez et al (2014) showed that a faith-based diabetes prevention program can lead to increasing physical activity, and eating more fruit and less fast food in diabetic patients. Muslims believe that God created human beings and gave them bodies that should be cared for (Aghamohammadi-Kalkhoran et al 2012). Many diabetic religious patients believe their body is a divine gift from God, and so they have an obligation to care for their body by controlling their daily life (Abdoli et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature review, Aghamohammadi-Kalkhoran (2012) employed hermeneutic phenomenology. [ 5 ] Faith plays a vital role in the perspective of believers of all faiths towards their illnesses. In this current study, the participants demonstrate a stage of having faith in Allah, gaining strength due to their linking the fact of having the disease to the will of Allah, for which they believe they will be rewarded.…”
Section: Discussionmentioning
confidence: 99%
“…They kept to medical advice, diet and exercise only when they felt that their blood sugar level was high. [ 5 ] This might be considered a wrong behaviour since they changed their diets for the purpose of reducing blood sugar only temporarily, and then back to their earlier dietary habits and activity levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation